Situation of Uterine Proplapse in Salyan, Mugu and Bajhang Districts of Nepal: A Clinic Based Study - Khatri, RB (Health Prospect, 2018)
Introduction: Uterine prolapse is a major public health problem in rural Nepal. It is a medical and social problem, deeply rooted with poor health services and socio-cultural beliefs. Prevention and management is crucial for maternal health. This study aimed to explore the situation of uterine prolapse problems and attempts of health response through mobile camps. Methodology: It is a mobile clinic based study of mobile reproductive health camps. Screening, laboratory investigation, treatment as well as preventive pressure were done at camps and screened cases were referred for hysterectomy. Follow up was done after three months of hysterectomy at respective camp sites. Results: Prevalence of uterine prolapse is 15% among women attending in clinic in three districts; high number of women having first degree and third degree uterine prolapse. Conclusion: There is urgent need of surgical treatment of UP. Promotive and preventive like behavior change communication interventions should focus to aware the people DOI: http://dx.doi.org/10.3126/hprospect.v10i0.5638 Health Prospect Vol.10 2011, pp.10-13